Pancasila Sebagai Sistem Filsafat - Raihanah Muttmainnah; Pebrienti Siregar; Bambang Trisno (International Forum of Researchers and Lecturers, 2024)
Pancasila, as the state foundation and ideology of the Indonesian nation, not only functions as a guide to national and state life, but also as a philosophical system that underlies the outlook on life, ideals and values ​​held by Indonesian society. As a philosophical system, Pancasila contains five interrelated principles and forms an integral framework for thinking. These five precepts reflect universal noble values ​​and contain moral principles that can be applied in various aspects of life. This study aims to analyze Pancasila as a philosophical system, explore the deep meaning of each principle, and understand its relevance and application in the context of modern life. Through a philosophical approach, it is hoped that this research can strengthen understanding of Pancasila as a moral and ethical foundation, as well as a guide in developing a just, prosperous and dignified society.